Peran Kelompok Tani Dalam Meningkatkan Kesejahteraan Petani Sawit di Desa Marga Mulia Kecamatan Kikim Timur Kabupaten Lahat - Rokhim, Anggi Baitul (Universitas Bojonegoro, 2023)
The aim of these research to: 1) To determine the role of Farmer Groups in Marga Mulia Village, Kikim Timur District. 2) To determine the level of income and welfare of oil palm farmers in Marga Mulia Village, Kikim Timur District. 3) Analyze the relationship between the role of farmer groups and the level of welfare of oil palm farmers in Marga Mulia village, Kikim timur, Lahat district. This research was conducted in Marga Mulia Village, Kikim Timur District. The location of this research was chosen deliberately. Data collection was carried out in December 2020. The research method used in this study is the survey method. The sampling method in this research is the Slovin method. The results showed that the role of the oil palm farmer groups in Marga Mulia Village was sufficient or moderate. The average income of oil palm farmers in Marga Mulia Village per hectare is IDR15,439,808,-ha/year. Based on the research results, the income of oil palm farmers in Marga Mulia village is higher than the poverty rate in South Sumatra and has an increase in the welfare of oil palm farmers in Marga Mulia Village by 90 percent. Based on statistical tests using the SPSS tool, the role of oil palm farmer groups with Welfare Levels obtained significant results with a significant value of 0.046<0.05, which means that there is a significant relationship between the variabel role of farmer groups and the level of welfare with a correlation coefficient value of 0.318 which means that according to Gofar it has The strength of the relationship is low/weak because the value of the positive correlation coefficient means that the relationship is unidirectional, that is, if one variabel increases then the other variabel also increases.